2011
DOI: 10.22499/2.6102.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rainfall drivers and teleconnections in an ACCESS AMIP run

Abstract: This study examines teleconnections from the El Niño Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the Southern Annular Mode (SAM), and atmospheric blocking to rainfall over the Australian continent. The analysis is carried out for observations and an atmospheric GCM driven by prescribed time-varying sea surface temperatures. The model rainfall teleconnection to the blocking index is well captured in each season, whereas the IOD rainfall teleconnection is only weakly evident in the model. The ENS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…We used this framework rather than coupled global climate models (GCMs) as previous studies have shown that coupled models underestimate the MSLP response to external forcings (Gillett et al 2003(Gillett et al , 2005Gillett and Stott 2009;Barkhordarian 2012;Bhend and Whetton 2013) and underestimate atmospheric blocking (Scaife et al 2010;Flato et al 2013). Models with lower biases, including atmosphere-only models, have been shown to perform better (Scaife et al 2010;Risbey et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…We used this framework rather than coupled global climate models (GCMs) as previous studies have shown that coupled models underestimate the MSLP response to external forcings (Gillett et al 2003(Gillett et al , 2005Gillett and Stott 2009;Barkhordarian 2012;Bhend and Whetton 2013) and underestimate atmospheric blocking (Scaife et al 2010;Flato et al 2013). Models with lower biases, including atmosphere-only models, have been shown to perform better (Scaife et al 2010;Risbey et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall over Australia is strongly affected by sea surface temperature as well as other climatic and weather drivers (Risbey et al 2011). Hence, we first compare the AMIP style simulations, 1.0A and 1.3A, to observations, thus excluding any effects of the coupled model calculated SST anomalies and associated feedbacks between the ocean and the atmosphere.…”
Section: Precipitation and Screen Temperature Biases Over Australiamentioning
confidence: 99%
“…The patterns of precipitation are very similar to the AMIP runs but overall there is more precipitation in both 1.0C and 1.3C in both seasons in the centre of the continent but not in the coastal areas and Cape York Peninsula. In 1.3C the more intense summer rainfall along the east coast has retreated showing that the more intense easterly flow events generating the rainfall (Risbey et al 2011) are not captured by the coupled model. Figure 13 compares the simulated mean screen-level temperature from the AMIP simulation with ERA-interim reanalysis.…”
Section: Precipitation and Screen Temperature Biases Over Australiamentioning
confidence: 99%
“…17(b, c)) is compared with that in the Bureau of Meteorology rainfall dataset (Fig. 17(a)); the rainfall teleconnection in the AMIP simulation with an earlier version of the ACCESS atmosphere model was investigated by Risbey et al (2011). distributions. The coupled models also do a reasonable job in simulating the ENSO-induced pressure patterns, with some exceptions.…”
Section: Enso Teleconnectionsmentioning
confidence: 99%